Valeria Manzano, The Age of Youth in Argentina. Culture, Politics and Sexuality from Perón to Videla, Chapel Hill, The University of North Carolina Press, 2014 - ΖΕΣΤΑΝΑΚΗΣ, ΠΑΝΑΓΙΩΤΗΣ (Μνήμων, 2016)
Δεν παρατίθεται περίληψη στα ελληνικά.